2020
DOI: 10.1186/s13023-020-01590-7
|View full text |Cite
|
Sign up to set email alerts
|

Maple syrup urine disease in Brazilian patients: variants and clinical phenotype heterogeneity

Abstract: Background Maple syrup urine disease (MSUD) is an autosomal recessive inherited metabolic disease caused by deficient activity of the branched-chain α-keto acid dehydrogenase (BCKD) enzymatic complex. BCKD is a mitochondrial complex encoded by BCKDHA, BCKDHB, DBT, and DLD genes. MSUD is predominantly caused by Variants in BCKDHA, BCKDHB, and DBT genes encoding the E1α, E1β, and E2 subunits of BCKD complex, respectively. The aim of this study was to characterize the genetic basis of MSUD by identifying the poin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
10
2
Order By: Relevance
“…In terms of genetic variants detected, the proportion of patients with biallelic variants in BCKDHB is much larger than the reported in the Mennonite population (Strauss et al, 2020). Malaysian, Egyptian and Brazilian populations also show a predominance of biallelic variants in BCKDHB, being associated with 45-55% MSUD cases (Ali & Ngu, 2018;Khalifa et al, 2020;Margutti et al, 2020). Nevertheless, our population shows an even higher frequency of these variants.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In terms of genetic variants detected, the proportion of patients with biallelic variants in BCKDHB is much larger than the reported in the Mennonite population (Strauss et al, 2020). Malaysian, Egyptian and Brazilian populations also show a predominance of biallelic variants in BCKDHB, being associated with 45-55% MSUD cases (Ali & Ngu, 2018;Khalifa et al, 2020;Margutti et al, 2020). Nevertheless, our population shows an even higher frequency of these variants.…”
Section: Discussioncontrasting
confidence: 61%
“…This variant has a Spanish origin but with a low reported frequency in that population (Rodríguez-Pombo, Navarrete, Merinero, G omez-Puertas, & Ugarte, 2006). In Brazil, the allelic frequency of the same variant was almost 10-fold lower (0.05) than in our cohort, and the p.Pro200Ter in BCKDHB was also less frequent in that population (0.12 in Brazil, 0.17 in Chile) (Margutti et al, 2020). Although it was not possible to identify other Latin American cohorts genetically tested, we can infer that the genetic architecture of Chilean MSUD cohort differs widely from other studied populations.…”
Section: Discussioncontrasting
confidence: 60%
“…This study cohort included 21 MSUD patients (classic subtype). Other studies included nearly similar numbers of children with MSUD (classic subtype) ranging from 6 to 37 children (Cheng et al, 2017;Lee et al, 2008;Margutti et al, 2020;Yunus et al, 2012) (Strauss et al, 2020). In this study, the mean age of onset of symptoms to appear was mean 8.3 ± 6.9 days (range: 3-75 days).…”
Section: Discussionmentioning
confidence: 66%
“…This study cohort included 21 MSUD patients (classic subtype). Other studies included nearly similar numbers of children with MSUD (classic subtype) ranging from 6 to 37 children (Cheng et al, 2017 ; Lee et al, 2008 ; Margutti et al, 2020 ; Yunus et al, 2012 ). The largest study for MUSD children was the one done by Strauss et al who reported 184 MSUD children {including 176 children (95.7%) having the classic subtype} (Strauss et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation